2013
DOI: 10.1186/1749-7922-8-46
|View full text |Cite
|
Sign up to set email alerts
|

The role of red cell distribution width in the diagnosis of acute appendicitis: a retrospective case-controlled study

Abstract: PurposeThe aim of this study was to seek whether red cell distribution width (RDW) has a role in the diagnosis of acute appendicitis. It was also aimed to show the relationship of RDW with leukocyte count and C-reactive protein (CRP) level.MethodsThis study was conducted via retrospective assessment of the hospital records of the adult patients who were operated for acute appendicitis between January 2010 and February 2013 and had a pathology report that confirmed the diagnosis of acute appendicitis. The patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
50
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 22 publications
(31 reference statements)
2
50
3
2
Order By: Relevance
“…Additionally, It was found to be related to mortality and other severe adverse outcomes in infectious diseases (28). Nowadays, different authors have been studied as an inflammatory marker in AA (8,15,16) however the results are limited and contradictory. Narci et al (15) observed that RDW levels were significantly lower in cases with AA than healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, It was found to be related to mortality and other severe adverse outcomes in infectious diseases (28). Nowadays, different authors have been studied as an inflammatory marker in AA (8,15,16) however the results are limited and contradictory. Narci et al (15) observed that RDW levels were significantly lower in cases with AA than healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, different authors have been studied as an inflammatory marker in AA (8,15,16) however the results are limited and contradictory. Narci et al (15) observed that RDW levels were significantly lower in cases with AA than healthy subjects. In contrast, Bozlu et al (16) found the higher levels of RDW in children with AA compared with control groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Şenol et al (5) emphasized that a high RDW value on admission is an independent marker of mortality in patients with acute pancreatitis and might be used as a prognostic marker. Narci et al (33) stated that RDW levels in an AA group were low when compared with a control group, and they therefore cannot be used as a suitable marker. They detected a sensitivity of 47% and a specificity of 67% when the optimum cut-off value was 15.6% according to ROC analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Increased RDW-level has been shown to be associated with elevated CRP, erythrocyte sedimentation rate, and interleukin-6 levels (22, 25, 27). Narci et al (28) determined decreased RDW level in patients with acute appendicitis with a sensitivity and specificity of 47% and 67%, respectively. However, the difference was so slight that it was concluded that RDW could not be used in diagnostic testing.…”
Section: Discussionmentioning
confidence: 99%